(untitled) (Research, Society and Development, 2019)
The purpose of this article is to present the role of the tutor in the Multiprofessional Residency Program in Physical Rehabilitation in a private institution of Brazilian education through an experience report. The tutor has the function of supporting resident students by teaching techniques and skills to provide interdisciplinary assistance to people with some physical impairment, be it temporary or permanent in the various rehabilitation care settings. It is concluded that the role of the tutor is fundamental in the teaching-learning process, since it contributes in an important way in the qualification of the professionals for interdisciplinary action assisting in the ethical, human and technical-scientific improvement, as well as for the integral health care of the people, families and communities.